Centrosome & centriole - Gomes, Renata Maria de Almeida Bastos; Oegema, Karen (Methods in cell biology, 2015)
This new volume of Methods in Cell Biology looks at methods for analyzing centrosomes and centrioles. Chapters cover such topics as methods to analyze centrosomes, centriole biogenesis and function in multi-ciliated cells, laser manipulation of centrosomes or CLEM, analysis of centrosomes in human cancers and tissues, proximity interaction techniques to study centrosomes, and genome engineering for creating conditional alleles in human cells